EFEKTIVITAS PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) TERHADAP KESEJAHTERAAN KELUARGA PENERIMA MANFAAT (KPM) DI KELURAHAN SUNGAI MEMPURA KECEMATAN MEMPURA - Yusherly Kurnia Ningsih A (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2024)
This study discusses the effectiveness of the non-cash food assistance program (BPNT) on the welfare of Beneficiary Families (KPM) in Sungai Mempura Village, Mempura District. This study was motivated by the phenomenon that the BPNT program has not been targeted appropriately, as the community feels that the assistance is not distributed fairly, causing social jealousy. The program in question is BPNT (Non-Cash Food Assistance), which is a government effort to alleviate poverty by providing non-cash food assistance to Beneficiary Families (KPM) so that they can meet their nutritional and food needs in a targeted, timely, and high-quality manner. The method used in this study is qualitative with a descriptive method, which involves data collection through interviews, observation, and documentation. The research subjects were Beneficiary Families (KPM) residing in Sungai Mempura Village and facilitators as mentors, while the research object focused on the effectiveness of the Non-Cash Food Assistance (BPNT) program on the welfare of Beneficiary Families (KPM). The results of the study show that the BPNT program in Sungai Mempura Village is effective in improving the welfare of Beneficiary Families (KPM), as seen from the indicators of the accuracy of the target recipients, increased access to nutritious food, and support for the commitment to implement the program. However, there were obstacles such as delays in the distribution of assistance, suboptimal updating of recipient data, and program monitoring and evaluation that needed to be improved so that the benefits of the program could be maximized. Overall, the BPNT program made a positive contribution to improving the welfare of Beneficiary Families (KPM), although there were still improvements to be made in the technical aspects of distribution and data management.